(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
The article discusses the main trends in methodological approaches to English language proficiency and language achievement assessment and elaborates testing and assessment techniques to align reliable and fair assessment techniques with English language learning based on international CEFR standard of evaluating language competencies and national standards of educational and training curriculum. The study aims to reflect the advancements and shortcomings in structural and communicative approaches to English language assessment backed up with research findings from foreign and contemporary scholars’ literature review. As a result, researched comprehensive models of language assessment tasks in terms of objective and subjective tests and analysis of documents in the implementation of language proficiency assessment into continuous education, especially higher specialized education, help extend the scope of innovative studies in the field of communicative English language teaching and testing.